Analisa Faktor Penentu Keputusan Nasabah Pegadaian Memilih Pegadaian Syariah sebagai Alternatif Solusi Masalah Keuangan: Studi Empiris di Kota Depok - Mujakir; Siti Aisyah (Tathawwur: Jurnal Ekonomi Pembangunan dan Keuangan Islam, 2024)
This study aims to determine the 7ps of the marketing mix (product, price, promotion, place, people, process & physical evidence on people's decisions to choosing sharia pegadaian as alternative solutions to financial problems: an empirical study on sharia pegadaian customers in Depok city. This study uses primary data in the form of a questionnaire containing statements related to the variables studied to sharia pegadaian customers as respondents. This study used Partial Least Square (PLS) Structural Equation Modeling (SEM) analysis with a sampling technique using a purposive sampling method assisted by the statistical tool SmartPLS 4. The results of this study indicate that the variable product, price, promotion, process and Physical Evidence have a significant effect on people's decision to choose sharia pegadaian as a financial solution, while the place and people variables have no effect on people's decisions to choose sharia pegadaian as a financial solution in Depok City.